Enhancing Ultra-High Temperature Milk Quality: A Novel Approach to Microbial Contamination Detection Using the BD BACTEC™ FX System - Isabella Maria Fernandes Botelho Moreira; Jaqueline Aparecida Honorato; Rafaela da Silva Rodrigues; Solimar Gonçalves Machado; Antonio Fernandes de Carvalho (Journal of Food Protection)
The demand for effective detection methods to ensure the safety and quality of Ultra-High Temperature (UHT) milk remains crucial in the food industry. Traditional techniques for detecting microorganisms are time-consuming and labor-intensive, leading to a need for a rapid and sensitive method for detecting microbial growth in UHT milk. This study evaluates the efficacy of the BD BACTEC™ FX system for microbial detection in UHT milk samples. The system utilizes internal fluorescent CO2 sensors to detect the metabolic activity of bacteria growing in the culture broth. The investigation comprises two stages: a controlled laboratory experiment with UHT milk samples spiked with Bacillus spizizenii inoculated at different population levels (from 0 to 4.0 log10 CFU/mL), and an industrial-scale assessment of commercial UHT milk. The microbial detection system detected the lowest B. spizizenii count (0 log CFU/mL) inoculated into UHT milk after 13 h of incubation. The 13-hour incubation period was also sufficient to detect microbial contamination in commercial UHT milk samples. Results indicate that this system offers heightened sensitivity compared to conventional methods, detecting microbial contamination in a significantly shorter time frame (6–13 h). Taxonomic identification of contaminants revealed the presence of Cellulomonas spp. and Enterococcus spp. in UHT commercial samples. The findings emphasize the critical importance of robust detection techniques in ensuring the safety and quality of UHT milk products.